THE ROLE OF TRANSCRIPTION IN ARABIC LOANWORDS (Conferences, 2026)
This article analyzes the phonetic and morphological adaptation features of the transcription symbols adopted in order to make the letters characteristic of this language in other languages, especially in Uzbek, understandable to the reader. In the study, the expression of sounds that are present in Arabic but not in other languages ​​through transcription is highlighted based on examples.